Changes in Cardiac Morphology and Function in Individuals With Diabetes Mellitus: The UK Biobank Cardiovascular Magnetic Resonance Substudy. (September 2019) - Jensen, Magnus T.; Fung, Kenneth; Aung, Nay; Sanghvi, Mihir M.; Chadalavada, Sucharitha; Paiva, Jose M.; Khanji, Mohammed Y.; de Knegt, Martina C.; Lukaschuk, Elena; Lee, Aaron M.; Barutcu, Ahmet; Maclean, Edd; et al.
Abstract : Background: Diabetes mellitus (DM) is associated with increased risk of cardiovascular disease. Detection of early cardiac changes before manifest disease develops is important. We investigated early alterations in cardiac structure and function associated with DM using cardiovascular magnetic resonance imaging. Methods: Participants from the UK Biobank Cardiovascular Magnetic Resonance Substudy, a community cohort study, without known cardiovascular disease and left ventricular ejection fraction ≥50% were included. Multivariable linear regression models were performed. The investigators were blinded to DM status. Results: A total of 3984 individuals, 45% men, (mean [SD]) age 61.3 (7.5) years, hereof 143 individuals (3.6%) with DM. There was no difference in left ventricular (LV) ejection fraction (DM versus no DM; coefficient [95% CI]: −0.86% [−1.8 to 0.5]; P =0.065), LV mass (−0.13 g/m 2 [−1.6 to 1.3], P =0.86), or right ventricular ejection fraction (−0.23% [−1.2 to 0.8], P =0.65). However, both LV and right ventricular volumes were significantly smaller in DM, (LV end-diastolic volume/m 2 : −3.46 mL/m 2 [−5.8 to −1.2], P =0.003, right ventricular end-diastolic volume/m 2 : −4.2 mL/m 2 [−6.8 to −1.7], P =0.001, LV stroke volume/m 2 : −3.0 mL/m 2 [−4.5 to −1.5], P <0.001; right ventricular stroke volume/m 2 : −3.8 mL/m 2 [−6.5 to −1.1], P =0.005), LV mass/volume: 0.026 (0.01 to 0.04) g/mL, P =0.006. Both left atrial and right atrial emptying fraction were lower in DM (right atrial emptying fraction: −6.2% [−10.2 to −2.1], P =0.003; left atrial emptying fraction:−3.5% [−6.9 to −0.1], P =0.043). LV global circumferential strain was impaired in DM (coefficient [95% CI]: 0.38% [0.01 to 0.7], P =0.045). Conclusions: In a low-risk general population without known cardiovascular disease and with preserved LV ejection fraction, DM is associated with early changes in all 4 cardiac chambers. These findings suggest that diabetic cardiomyopathy is not a regional condition of the LV but affects the heart globally.